A Simultaneous Photofragment Spectroscopy Measurement of Rovibronic and Translational Excitation in the CH3l A–Band Photodissociation System. Issue 4 (1988) - Black, John F.; Powis, Ivan
Abstract : The methyl iodide A-band photodissociation is investigated using a photofragment time-of-flight technique coupled with state specific detection of either the iodine atom or methyl radical dissociation products by multiphoton ionization. The method is quite general and allows the fragments' velocity and spatial distributions to be determined simultaneously with their rotational, vibrational and electronic excitation. It is shown that methyl product from two competing dissociation channels, one direct, the other necessitating an initial surface crossing, can be clearly distinguished by virtue of the characteristic translational excitation in each. The different rotational excitation which is observed in these two channels is discussed in terms of the dissociation dynamics in the methyl iodide A-band continuum.